The Relationship Between Intolerance of Uncertainty and Anxiety about the Future in Gen Z is Mediated By Family Support - Putri, Hamulia Syawalita; Andik Matulessy; Amanda Pasca Rini (Kirana Publisher (KNPub), 2025)
This study aims to explore the relationship between Intolerance of Uncertainty (IU) and future anxiety among Gen Z, considering family support as a mediator. IU is defined as an individual's inability to cope with negative responses arising from a lack of critical information, exacerbated by uncertainty. Future anxiety refers to feelings of fear, worry, and unease about undesirable possibilities, while family support involves attitudes of acceptance and assistance among family members. The study employs a quantitative correlational method with 348 Gen Z respondents in Surabaya as the research subjects.The findings reveal that family support serves as a mediator in the indirect relationship between IU and future anxiety (z = 2.661, p = 0.008). Additionally, a significant direct relationship exists between IU and future anxiety, where higher IU corresponds to greater future anxiety among Gen Z (z = 5.611, p = 0.001). A negative relationship is found between IU and family support, indicating that increased IU reduces family support (z = -2.798, p = 0.005). Meanwhile, family support is significantly associated with reduced future anxiety (z =-8.633, p = 0.001).These findings highlight the crucial role of family support in mitigating the impact of IU on future anxiety, providing valuable insights for interventions aimed at improving the psychological well-being of Gen Z.